Extração da pectina da fibra bruta do caju: caracterização química da fração insolúvel. - ALMEIDA, G. É. P. DE (2025)
The increase in cashew nut production results in a greater generation of a byproduct of nut processing: cashew apple (Anacardium occidentale L.), a raw material used in several products. However, its industrial processing for juice extraction generates a large volume of agro- industrial waste, known as cashew apple bagasse (CAB), which is often underutilized or completely discarded. Due to its composition rich in dietary fiber, CAB has been recognized as a promising source of pectin, a polysaccharide of commercial value for the food, beverage, and pharmaceutical industries. Moreover, the pectin extraction process generates an additional waste product: the insoluble fraction of cashew apple (IFCA). To date, few detailed studies have been conducted on this insoluble fraction isolated from pectin extraction, which could aid in evaluating the feasibility of obtaining both products simultaneously. The present study aimed to isolate the insoluble fraction of the cashew apple through pectin extraction, perform its chemical characterization, and compare its properties with those of raw bagasse. To achieve this, protein and lipid analyses were conducted, revealing that the insoluble fraction retained values similar to those of untreated CAB. Moisture and water activity (W a ) analysis showed that both drying processes applied were efficient, resulting in a final product with moisture content below 5% and W a <0,4, which is essential for long-term preservation. Ash content also exhibited no significant variation. The fiber composition was obtained through lignocellulosic analyses, including extractives, lignin, holocellulose, alpha-cellulose, and hemicellulose content. The results indicated that although the pectin extraction treatment caused a slight reduction in these components (<5%), the final residue contained nearly twice the fiber concentrations observed in raw bagasse, demonstrating a greater enrichment in insoluble fibers. FTIR analysis confirmed the presence of lignocellulosic compounds and supported the efficient extraction of pectin. Additionally, color analysis showed a considerable variation in this parameter, indicating that the applied processes resulted in a darker final product. It is expected that the findings of this study will contribute to the search for new viable applications for this residue, promoting the valorization of an additional byproduct within the cashew production chain.